The mediating and moderating effects of top management support on the cloud ERP implementation–financial performance relationship - Jayeola, Olakunle; Sidek, Shafie; Abdul Samad, Zulkiflee; Hasbullah, Nornajihah Nadia; Anwar, Saiful; Binh An, Nguyen; Nga, Vu Thi; Al-Kasasbeh, Omar; Ray, Samrat (Multidisciplinary Digital Publishing Institute, 2022)
Cloud enterprise resource planning (ERP) is one of the most sought-after information technology (IT) solutions for improving business performance due to its affordability, scalability, and pay-per-use subscription model. The impact of cloud ERP implementation on business performance, on the other hand, remains inconclusive. Additionally, an important factor that transverses all organizational processes, including IT implementation, is top management support (TMS). However, the TMS’s role in the latter stage (business value realization) of cloud ERP implementation is unclear. The purpose of this paper is to examine the mediating and moderating impacts of top management support (TMS) on the relationship between cloud ERP implementation and financial performance. A total of 204 small and medium enterprises (SMEs) in Malaysia were surveyed, and data analysis was conducted using partial least square structural equation modelling (PLS-SEM). The results demonstrate that TMS plays a partial mediating role in the relationship between cloud ERP implementation and financial performance and that this relationship is significantly stronger in SMEs with low TMS levels. As a result, it is concluded that top management should provide the required support following successful cloud ERP implementation in order to achieve positive financial results. However, such support must be adjusted in order to avoid the deterioration of the firm’s financial performance.